Deficit of nature as a manifestation of a hidden curriculum of the school. Poznan educational studies 2021 - Kozłowska, Agnieszka; Chmura-Rutkowska, Iwona; Buchnat, Marzena Agnieszka; Cybal-Michalska, Agnieszka; Cytlak, Izabela; Jaskulska, Sylwia; Kanclerz, Bożena; Marciniak, Mateusz; Myszka-Strychalska, Lucyna; Szafran, Joanna Maria; Wawrzyniak-Beszterda, Renata Maria (Fundacja Pedagagium, 2022)
Poznan educational studies 2021, conducted to improve Poznan city’s educational policy for the next ten years, covers several areas of students’ school experience. The study focuses on the area of ecology and one aspect of it: students’ contact with nature. The study aimed to find out whether Poznan students are exposed to nature deficit and thus at risk of developing nature deficit syndrome. 996 students from primary and secondary Poznan schools were surveyed online in the Poznan educational studies project. Five questions from the questionnaire were used in this study. Basic statistics and Chi-square tests were conducted in data analysis, using row data based on the survey. The study proved the nature deficit syndrome in the analyzed group of students. Only 14% of them experienced lessons outside the school building during their school lives. This fact is interpreted in the paper in the context of Jackson’s concept of the hidden curriculum and Eisner’s concept of the null curriculum. It also referred to the concepts of deficit of nature disorder and the hypothesis of biophilia.
Deficyt natury jako przejaw ukrytego programu szkoły. Poznańskie badania oświatowe 2021
Keywords: deficit of nature; nature-based learning; hidden curriculum; null curriculum; school space